Analisis Morfologi Partikel Mikrostruktur Geopolimer Abu Sekam Padi Menggunakan Pembakaran Dengan Alat Furnace Dan Pembakaran Secara Manual - Cut Yusnar (Jurnal Serambi Engineering, 2024)
The morphology of Rice Husk Ash (RHA) geopolymer microstructure particles obtained by using a kiln at a temperature of 700oC produces a grain shape that is different from the RHA material burned by hand. Theshape of the microstructure particles for geopolymer concrete paste determines the strength of the geopolymer range. The research results show that the shape of the granules obtained by firing in a kiln has a crystalline shape Meanwhile, the shape of the particles obtained by manual firing is amorphous. Theresults of compressive strength tests with amorphous particle structures have greater compressive strength than those in crystalline form. This is demonstrated by testing the RHA furnace material and manually using SEM (Scanning Electron Microscopy) and XRD (X-Ray Diffraction) tests, which show that the granules obtained from furnace burning are crystalline and those obtained from manual burning are amorphous. Crystalline particles are more difficult to react with than amorphous particles in geopolymer concrete mixes. The XRD test results show the highest diffraction by the silica element. The chemical content of silica elements in rice husk ash was found to be 94.9%.